2014
DOI: 10.1186/1476-069x-13-102
|View full text |Cite
|
Sign up to set email alerts
|

PM2.5 in Beijing – temporal pattern and its association with influenza

Abstract: BackgroundAir pollution in Beijing, especially PM2.5, has received increasing attention in the past years. Despite Beijing being one of the most polluted cities in the world, there has still been a lack of quantitative research regarding the health impact of PM2.5 on the impact of diseases in Beijing. In this study, we aimed to characterize temporal pattern of PM2.5 and its potential association with human influenza in Beijing.MethodsBased on the data collected on hourly ambient PM2.5 from year 2008 to 2013 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
87
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(98 citation statements)
references
References 44 publications
8
87
1
2
Order By: Relevance
“…Moreover, this impact was characterized by an evident dosage effect, a lag effect and a cumulative effect. Many studies showed that air pollution could cause a high incidence of respiratory disease (Gordon et al, 2014;Liang et al, 2014;Xu et al, 2013), but the manner in which it impacts diseases of the digestive tract with the hand-mouth approach as the primary route of transmission is unknown. The research team led by Professor Jiang from Peking University described one possibility in their latest study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this impact was characterized by an evident dosage effect, a lag effect and a cumulative effect. Many studies showed that air pollution could cause a high incidence of respiratory disease (Gordon et al, 2014;Liang et al, 2014;Xu et al, 2013), but the manner in which it impacts diseases of the digestive tract with the hand-mouth approach as the primary route of transmission is unknown. The research team led by Professor Jiang from Peking University described one possibility in their latest study.…”
Section: Discussionmentioning
confidence: 99%
“…Influenza cases were defined according to Technical guides for prevention and control of influenza issued by China Ministry of Health (http://www.moh.gov.cn/zwgkzt/s9491/200802/38820.shtml): sudden onset of fever ≥ 38°C, cough or sore throat, and absence of other diagnoses. As influenza is a notifiable disease (Class C), sentinel hospitals are required to collect nasopharyngeal swabs for each identified case which are subsequently sent to designated laboratories for virus isolation and further identification and results are submitted online within 24 h (Liang et al, 2014;Shu et al, 2010).…”
Section: Influenza Datamentioning
confidence: 99%
“…Of particular concern, both nationally and globally, is the increasing threat posed by emerging infectious diseases (e.g., severe acute respiratory syndrome [SARS] and the highly pathogenic avian influenza [HPAI]) in the Chinese population, both of which pose a significant public health threat (Wang et al, 2008). Few studies have examined the possible effect of ambient PM 2.5 concentrations on risk of communicable disease in China, but those that have reported a positive association between ambient Environment International 98 (2017) 82-88 PM 2.5 and localised transmission of influenza (C. Huang et al, 2016;Liang et al, 2014). However, until now there has been no large-scale examination of the association due to past unavailability of PM 2.5 data and incident cases of influenza at the national level.…”
Section: Introductionmentioning
confidence: 99%
“…Although individual risk for mortality is low, a significant subset of infected patients develop pneumonia, the most lethal consequence of influenza (5). Those at the highest risk for infection and complications include pregnant women (6), the elderly (>65 y) (7), the very young (<5 y of age, and especially less than 2 y), smokers (8), those exposed to inhaled toxicants such as oxygen (9) and air pollutants (10), and patients with chronic illnesses such as diabetes and emphysema (11,12). Increased risk is often ascribed to impairment of the immune system, and differential susceptibility of the airway epithelium is seldom considered in mechanistic studies of host factors that predispose to IAV infection and poor outcomes.…”
mentioning
confidence: 99%